2010
DOI: 10.18632/aging.100250
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms associated with type 2 diabetes in familial longevity: The Leiden Longevity Study

Abstract: Human longevity is in part genetically determined, and the insulin/IGF-1 signal transduction (IIS) pathway has consistently been implicated. In humans, type 2 diabetes is a frequent disease that results from loss of glucose homeostasis and for which new candidate polymorphisms now rapidly emerge from genome wide association studies.In the Leiden Longevity Study (n=2415), the offspring of long lived siblings (“offspring”) who are genetically enriched for longevity were shown to have a more beneficial metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
(20 reference statements)
2
18
0
Order By: Relevance
“…Furthermore, another critical gene under CMYC pathway such as TMEFF2 [42] (transmembrane protein with EGF-like and two follistatin-like domains 2) was down in the meditated cohort. Genetic variation of TMEFF2 has been shown to affect human longevity [43]. Fourth, in our study P38 MAPK, a key regulator of pro-inflammatory cytokine biosynthesis which induces low-grade chronic inflammation associated with aging was found to be affected by MBT program.…”
Section: Discussionsupporting
confidence: 47%
“…Furthermore, another critical gene under CMYC pathway such as TMEFF2 [42] (transmembrane protein with EGF-like and two follistatin-like domains 2) was down in the meditated cohort. Genetic variation of TMEFF2 has been shown to affect human longevity [43]. Fourth, in our study P38 MAPK, a key regulator of pro-inflammatory cytokine biosynthesis which induces low-grade chronic inflammation associated with aging was found to be affected by MBT program.…”
Section: Discussionsupporting
confidence: 47%
“…However, adjustment for parental diabetes with onset at any age might lead to an even greater bias because the diagnosis of diabetes is more likely in long-lived than short-lived individuals, and thus parental diabetes with an onset at any age mainly reflects length of life rather than genetic factors. To explain the association between family longevity and prevalence of type 2 diabetes, the frequency of 15 risk alleles known to be related to type 2 diabetes was compared between the offspring of nonagenarian siblings and the offspring's partners in the Leiden Longevity Study [13]. Although the offspring had a better glucose metabolism than their partners, there were no differences in the frequencies of any risk allele, and the mean numbers of risk alleles were virtually identical in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent epidemiological evidence for a relationship between longevity and lower rates of type-2 diabetes [11], yet previous evidence from the Leiden study (n=2415) and the Pilling et al 2016 Biobank longevity genetics Life Long Family Study (n=1562 in generation 1; n=3102 generation 2) suggested that offspring of long-lived participants do not have lower burden of type-2 diabetes risk alleles compared to their partners [10,25]. We also did not observe an association between the type 2 diabetes GRS and longevity in the UK Biobank participants, although small effects cannot be excluded.…”
Section: Comparison With Previous Workmentioning
confidence: 96%